Creativity, age and gender as predictors of academic achievement among undergraduate students - Naderi, Habibollah; Abdullah, Rohani; Tengku Abdul Hamid, Tengku Aizan; Jamaluddin, Shahrir; Mallan, Vijay Kumar (Marsland Press, 2009)
This study examined creativity, age and gender as predictors of academic achievement. Participants (N= 153, 105 = male & 48= female) completed creativity test. Cumulative grade point average (CGPA) was used to select the participants. A multiple regression analysis revealed creativity, age and gender explained 0.143 of the variance in academic achievement. The significance level was indicated by the F- value of 8.294. Multiple regression analysis showed interaction effects between creativity, age and gender as low predictors of academic achievement. The findings also show a lower correlation of CGPA and the independent variables of this study. No significant difference between CGPA and gender was observed. However implications of the findings to investigate in creativity, age and gender are discussed.